Unsteady three-dimensional MHD flow due to impulsive motion with heat and mass transfer past a stretching sheet in a saturated porous medium - Rajagopal, K.; Veena, P.H.; Pravin, V.K. (Zielona Góra: Uniwersytet Zielonogórski)
The development of velocity, temperature and concentration fields of an incompressible viscous electrically conducting fluid, caused by impulsive stretching of the surface in two lateral directions and by suddenly increasing the surface temperature from that of the surrounding fluid in a saturated porous medium is studied. The partial differential equations governing the unsteady laminar boundary layer flow are solved analytically.
Keywords: unsteadiness; laminar flow; three dimensional; shear stress; heat transfer; mass transfer; short-time solution; long-time solution